Clinical-epidemiological characterizationofophthalmological diseases in two Ecuadorian rural communities - Legrá Nápoles, Seydel; González Granda, Mayra Elizabeth; Acosta Cela, Johanna Alejandra (Revista Universidad de Guayaquil, 2016)
Some eye problems can cause loss of permanent vision. For residents of communities far from health centers, it is difficult to have professional help, a situation that causes late diagnoses that can result in irreversible visual disability in this population. The objective of the article is to characterize from the clinical and epidemiological point of view the ophthalmological diseases in two rural Ecuadorian communities. A descriptive, cross - sectional observational study was conducted in the communities of Constantino Fernández and Santa Rosa, Tungurahua province, during the March - July 2017 period. The clinical history was used as a source of information collection in the investigation. As a result, it was observed that the patients who most frequently attended the ophthalometric examination were those in the 21–30-year age group with a predominance of females. Normal visual acuity predominated in both eyes and ametropic patients prevailed. The presbyopic population was highlighted as the most relevant optometric affectation followed by astigmatism, while the ophthalmological affectation that predominated was the pterygium. The treatments indicated in order of frequency were ophthalmic lens, ophthalmic lens for reading and referral to the ophthalmologist. It is concluded that although most of the patients had a normal visual acuity, they need to have at their reach the necessary medical services for an adequate eye health surveillance, since it was observed optometric and ophthalmological alterations that can cause partial visual disability or total if the diagnosis is not early as it is: the refractive defects like astigmatism and within the ophthalmological diseases the pterygium and the cataracts.